Complexos organometálicos contendo carbenos N-heterocíclicos: síntese, caracterização e reatividade - Joao Andre Duarte Silva (2009)
In this work, some aspects of the chemistry of N-heterocyclic carbenes (NHC) are investigated. Charpter 1 presents a brief literature review comprising the historical aspects, the synthesis, the organometallic chemistry, and the stereo-electronic parameters of NHC, as wellas the applications of complexes containing NHC as ligands.In Charpter 2, aspects of the ring closing metathesis (RCM) of --dienes employing the second-generation Grubbs catalyst (a ruthenium complex containing an NHC ligand) as studied. The competition between acyclic diene metathesis polymerization (ADMET) andRCM was studied in detail. It was found that, starting from macrocyclic precursors, oligomers formed by ADMET are kinetically favored with respect to RCM products even at high dilutions. These oligomers are further converted in the desired RCM products, provided thecatalyst remains active and the reaction time is long enough, through a backbiting mechanism. The employment of NMR techniques to quantify the extension of RCM for macrocyclic and medium-ring precursors was critically analyzed. It was found that the results can be easilymisinterpreted due to the similarity between the intermediates (cyclic oligomers) and the starting materials or the final products. Although more advanced techniques such as DOSYNMR can help in resolving ambiguities in signal assignments, gas chromatography proved tobe a valuable ancillary tool for reliable quantification. This part of the work was developed in the laboratory of Dr. D. Fogg (chemistry Department University of Ottawa Canada). Major contributions were made by J. Conrad (RCM vs. ADMET) and S. Monfette (RCMquantification) and part of this work also integrates their Ph. D. thesis.In the Charpter 3, the complexation of various NHC and the tetranuclear iridium cluster [(-H)Ir4(CO)10(PPh2)] was studied. It was anticipated that the introduction of these exceptionally good electron donor ligands could significantly alter the electronic proprieties and, consequently, the scope of application of these compounds. Instead of the expectedligand exchange, however, the NHC promoted hydride abstraction to form the corresponding cationic imidazolium and anionic cluster [Ir4(CO)10(PPh2)]-. The ionic compound was isolated and characterized for four kinds of NHC. On the other hand, whenNBu4 +[Ir4(CO)11Br]- is used as starting material, after treatment with silver hexafluorophosphate in the presence of 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene(IPr), the cluster [Ir4(CO)11(IPr)] can be isolated. The (CO) in infrared spectra are displaced to lower wavenumbers in comparasion with the anionic cluster, demonstrating the strong electron-donor character of IPr.